True Covid-19 mortality rates from administrative data - Domenico Depalo (Global Labor Organization (GLO), 2020)
In this paper I use administrative data to estimate the number of deaths, the number of infections, and mortality rates from Covid-19 in Lombardia, the hot spot of the disease in Italy and Europe. The information is relevant for the policy maker, to make decisions, and for the public, to adopt appropriate behaviours. As the available data suffer from sample selection bias I use partial identification to derive these quantities. Partial identification combines as- sumptions with the data to deliver a set of admissible values, or bounds. Stronger assumptions yield stronger conclusions, but decrease the credibility of the inference. Therefore, I start with assumptions that are always satisfied, then I impose increasingly more restrictive assumptions. Using my preferred bounds, during March 2020 in Lombardia there were between 10,000 and 18,500 more deaths than before 2020. The narrowest bounds of mortality rates from Covid-19 are between 0.1% and 7.5%, much smaller than the 17.5% discussed for long time. This finding suggests that the case of Lombardia may not be as special as some argue.
Keywords: I18; C24; C81; 330; Covid-19; Mortality; Bounds